Gender shifts in the history of English - Curzan, Anne (Cambridge University Press, 2003)
Based on extensive research, Anne Curzan's study makes a major contribution by providing historical perspective on controversial questions regarding the continuing evolution of gender definition. How and why did grammatical gender gradually disappear from English and get replaced by a system where the gender of nouns and the use of personal pronouns depend on the natural gender of the referent? How is this shift related to "irregular agreement" (she for ships) and "sexist" language use (generic he) in Modern English? Finally, how is the language continuing to evolve 0n these respects?